2011
DOI: 10.4314/sajas.v41i2.71021
|View full text |Cite
|
Sign up to set email alerts
|

Non-genetic factors affecting growth performance and carcass characteristics of two South African pig breeds

Abstract: A study was conducted to establish non-genetic factors affecting growth and carcass traits in Large White and Landrace pigs. This study was based on 20 079 and 12 169 growth and 5 406 and 2 533 carcass data collected on performance tested pigs between 1990 and 2008 from Large White and Landrace breeds respectively. The traits analyzed were backfat thickness (BFAT), test period gain (TPG), lifetime gain (LTG), feed conversion ratio (FCR), age at slaughter (AGES), lean percentage (LEAN), drip-free lean percentag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
4
0
1
Order By: Relevance
“…Genetic improvement of these production traits relies on the proper adjustment of fixed effects. Some of the fixed effects in the literature known to affect production traits are age of dam, age at the beginning of test, herd of origin, year and season, sex and litter size (Ilatsia et al 2008;Dube et al 2011;Jafari et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic improvement of these production traits relies on the proper adjustment of fixed effects. Some of the fixed effects in the literature known to affect production traits are age of dam, age at the beginning of test, herd of origin, year and season, sex and litter size (Ilatsia et al 2008;Dube et al 2011;Jafari et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The various BF in different populations might cause by the difference in genetics, breed groups, ages and site at measurement, feed formular, feeding management and environmental conditions (i.e., open-house system or evaporative cooling system) including factors relating feed intake of the pigs. However, gilts in our population (CV 18%) had a slightly lower variation of BF than gilts in Philippines (Lego and Bondoc 2020), South Africa (Dube et al 2011), China (Hu et al 2016) and Korea (Alam et al 2021) which had CV ranged from 18.52 to 19.75% but other Landrace populations in Thailand, they had much higher variation of BF with CV of 25.90% (Imboonta et al 2007) and 28.81% (Wongsakajornkit and Imboonta 2015). The variation of BF in this population was in the range of BF as found in both tropical and temperate countries but more uniformity that implied to the e ciency of feeding program and well management under tropical condition.…”
Section: Discussionmentioning
confidence: 52%
“…Compared to temperate country, our gilts had a lower BF than Landrace (13.50 mm for BF at 100 kg) and Yorkshire (13.30 mm for BF at 100 kg) gilts in China (Hu et al 2016) and crossbred gilts (13.26 mm for BF at 29 weeks old) in Slovenia (Flisar et al 2012). Although gilts raised under cold whether seemed to have a higher BF than gilts raised under tropical climate, a high BF (15.60 mm for BF at 77 kg) was also performed in Landrace pigs in South Africa (Dube et al 2011), even in Thailand by Imboonta et al (2007) who reported 13.90 mm for BF at 22 weeks old in Landrace gilts. The various BF in different populations might cause by the difference in genetics, breed groups, ages and site at measurement, feed formular, feeding management and environmental conditions (i.e., open-house system or evaporative cooling system) including factors relating feed intake of the pigs.…”
Section: Discussionmentioning
confidence: 91%
“…Menurut Velayudan et al (2015) pakan sumber energi dibutuhkan ternak babi untuk fungsi pemeliharaan dan produksi. Dube et al (2011) mengemukakan bahwa tingkat manajemen peternakan babi yang optimum merupakan prasyarat untuk mencapai performans pertumbuhan dan kualitas hasil karkas yang optimum. Faktor yang mempengaruhi performans babi diantaranya adalah umur sapih.…”
Section: Pendahuluanunclassified